Position of the Working Group Sports Nutrition of the German Nutrition Society (DGE): Minerals and vitamins in sports nutrition - Carlsohn, A.; Braun, H.; Großhauser, M.; König, D.; Lampen, A.; Mosler, S.; Nieß, A.; Oberritter, H.; Schäbethal, K.; Schek, A.; Stehle, P.; Virmani, K.; et al. (Deutsche Zeitschrift für Sportmedizin, 2020)
Summary An adequate intake of minerals and vitamins is essential for health and performance of athletes. Depending on the type of sport and the intensity and scope of physical performance, as well as individual factors (such as dietary behavior, perspiration rate and composition of perspiration), athletes may be at increased risk of suboptimal micronutrient supply.